WLADYSLAW SZYMONOWICZ – ORGANIZER AND FIRST HEAD OF LVIV UNIVERSITY HISTOLOGY AND EMBRYOLOGY DEPARTMENT - Nadraga, M.S.; Lutsyk, A.D. (World of Medicine and Biology, 2019)
The article is devoted to the personality of Wladyslaw Szymonowicz, an outstanding Lviv histologist, founder and head of the Histology and Embryology Department (1897-1937), Dean of the Medical Faculty (1906-1907) of Lviv University. The life path of the scholar and his scientific activity, his publications on histological subjects are presented. Particular attention is paid to the world-famous manual on histology and microscopic anatomy of the human body, which has been reprinted 11 times in five languages: German, English, Italian, Polish, Spanish. The researcher's scientific interests included histology of sensory nerve endings, adrenal glands and the digestive system. Due to scientific and pedagogical activities of Wladyslaw Szymonowicz were trained five professors: S. Gzhytsky, L. Yaburek, B. Yalovy, B. Kalvariysky, B. Konopatska. The recognition of the researcher-histologist’s achievements is evidenced by his election as a full member of the Polish Academy of Arts and Sciences in Krakow and by his award of Lviv University Honored Professor.
Keywords: history of histology and embryology; histology manual; adrenal glands; sensory nerve endings